Aproximaciones al concepto de aprendizaje en cooperación y sus aportes a la pedagogía contemporánea (2016)
Textual typology and objective. This article is a product of the project: Assessment and transformation of the didactic strategy of dictation to optimize its contribution to the integral education of the French Language learner (Menet, 2016). It aims to elicit a reflection that allows establishing the communicating vessels between the pedagogical processes linked to processes of integral formation and the evolution of the human condition in their need for cooperation.Methodology. The approach is framed in the documentary research that from a hermeneutic vision, seeks to generate elements of discernment against the use of the concept of the cooperative as inherent to the origin and development of contemporary society and at the same time, it starts from the emerging pedagogy in which the theoretical approach is assigned to the research previously stated. The results of this conceptual in-depth has allowed to establish the relevance of incorporating an experiential vision of the values that underlie the formation of the citizens’ competences in the pedagogical processes. Therefore, and according to the evidence, the traditional system of education strengthened by an individualistic and competitive vision prevents learners from taking an assertive path towards integral formation, which becomes an ideal of educational institutions.Results. The contributions of learning in cooperation lead to rethinking the relevance given nowadays to competitive training and highlights the need for cooperation of pedagogical processes that become more than essential in a society focused on instrumental and productive aspects.